Increased immune cell infiltration in patient-derived tumor explants treated with Traniplatin: an original Pt(iv) pro-drug based on Cisplatin and Tranilast. Issue 60 (25th May 2018) - Lo Re, Daniele; Montagner, Diego; Tolan, Dina; Di Sanza, Claudio; Iglesias, Mar; Calon, Alexandre; Giralt, E.
Abstract : Traniplatin shows increased in vitro cytotoxic activity against colon and lung cancer cells but decreased activity against immune cells in comparison to Cisplatin. Abstract : Elevated intra-tumoral immune infiltrate is associated with an improved prognosis in cancer of distinct origins. Traniplatin (TPT) is a novel platinum(iv ) pro-drug based on Cisplatin (CDDP) and the marketed drug Tranilast. When compared in vitro to Cisplatin, TPT showed increased cytotoxic activity against colon and lung cancer cells but decreased activity against immune cells. In addition, TPT efficiency was evaluated in tumor explants derived from colorectal cancer samples from patients subjected to intended curative surgery. TPT induced strong intra-tumoral cytotoxic activity yet was associated with an elevated presence of immune cell infiltrate, suggesting a reduced cytotoxic activity against immune cells in colorectal cancer.